Conservation of plant biodiversity by biotechnology methods - N. V. Romadanova; S. V. Kushnarenko (Труды по прикладной ботанике, генетике и селекции)
Several methods of plant preservation are currently used in the Republic of Kazakhstan: 1) field gene banks in natural growing areas and pomological collections; 2) preservation of seeds at +4°С, –18°С, and –196°С; 3) сold storage of in vitro shoots at +4°С and +10 ± 2°С; 4) cryopreservation of plant tissues and organs at –196°C; 5) preservation of plant DNA at –80°C.Ex situ field collections of plants in Kazakhstan are maintained in botanical gardens of the Republic, arboretums, pomological gardens, nurseries, peasant and farm enterprises, and personal plots. The largest collection of fruit and berry plants is located in the Pomological Garden and includes about 4 thousand varieties, more than 40 thousand hybrids and wild forms of various crops.The Republic of Kazakhstan has about 42,000 accessions in the seed collection. The cereal crop collection is mainly concentrated in the Kazakh Research Institute of Agriculture and Plant Growing – 1/3 of the national genetic resources. The main seed collection of vegetable crops and potatoes (14,700 accessions) is held by the Kazakh Research Institute of Potato and Vegetable Growing. Collections are also available at the Institute of Botany and Phytointroduction and in the Institute of Plant Biology and Biotechnology (IPBB), with the storage mode of + 4°C and –18°C. IPBB also uses cryopreservation technology at –196°C for seed storage.The main in vitro collection of Kazakhstan is kept at the IPBB at + 4°С and +10 ± 2°С; it includes more than 140 accessions of various fruit, berry, nut, vegetable, ornamental, and woody crops, grapes, potatoes, etc. A cryogenic collection of seeds, shoot tips, dormant buds, and embryonic axes in liquid nitrogen (–196°C) is found only in IPBB. The collection includes more than 700 accessions.